A STUDY OF THE EFFECT OF SAUNA ON THE OXYGEN TRANSPORT FUNCTION OF YOUNG ATHLETES ENGAGED IN HANDBALL SPORT - Hokuma Mammadova Eyvaz,; Tarlan Mammadova Nasir, (International Journal of Innovative Technologies in Social Science, 2023)
The effect of sauna on blood oxygen transport function, lipid peroxidation, prooxidant-antioxidant balance in athletes aged 17-21 engaged in handball sport was studied in the article. Persons involved in the hot air sauna were exposed once a week (20 procedures) for a period of four months. The sauna procedure (at 85-90°C, 10-15% humidity) consisted of two parts: 5 and 10 minutes. In young handball athletes, after taking a dry air bath, an increase in pO2, which is the development of respiratory alkolosis, and a decrease in the combination of hemoglobin and oxygen in venous blood increased the amount of oxygen transported to tissues. After a one-time exposure to the sauna, the development of oxidative stess accelerated (intensification of free radical processes, weakening of antioxidant defenses), and at the end of the course it began to decline. The observed increase in the formation of nitric oxide can play an important role in the modification of oxygen-dependent processes in the body.